2011
DOI: 10.1111/j.1528-1167.2011.03264.x
|View full text |Cite
|
Sign up to set email alerts
|

Initiation of epileptiform activity in a rat model of periventricular nodular heterotopia

Abstract: Summary Purpose Periventricular nodular heterotopia (PNH) are, in humans, often associated with difficult-to-control epilepsy. However, there is considerable controversy about the role of the PNH in seizure generation and spread. To study this issue, we have used a rat model in which injection of methylazoxymethanol (MAM) into pregnant rat dams produces offspring with nodular heterotopia-like brain abnormalities. Methods Electrophysiological methods were used to examine the activity of the MAM-induced PNH r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
22
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 52 publications
3
22
0
2
Order By: Relevance
“…This speculation seems reasonable when considering a previous study using brain slices from model rats with PVNH. In that study, spontaneous discharges induced by bicuculline were time‐locked between the HN and the hippocampus, and the discharges were always initiated in the hippocampus, and not in the HN (Tschuluun et al., 2011).…”
Section: Discussionmentioning
confidence: 91%
“…This speculation seems reasonable when considering a previous study using brain slices from model rats with PVNH. In that study, spontaneous discharges induced by bicuculline were time‐locked between the HN and the hippocampus, and the discharges were always initiated in the hippocampus, and not in the HN (Tschuluun et al., 2011).…”
Section: Discussionmentioning
confidence: 91%
“…Abnormal connectivity between heterotopia clusters and the cortical and hippocampal regions has been shown using tract-tracing methods [74]. The focal abnormalities induced in this model are more than anatomical abnormalities; the surrounding tissue is also abnormal [75], and it has been suggested that this tissue is the initiator/driver of the epileptiform discharge [76].…”
Section: Methylazoxymethanol Acetatementioning
confidence: 80%
“…In some cases, heterotopic nodules can generate normal activity and may not be epileptogenic [9]. Furthermore, experimental data do not support the concept that NH lesions are the primary epileptogenic but rather point to the overlying cortex, which has been shown in a rat model [10]. Perhaps, the epileptogenicity of the dysplastic cortex is the main condition for generating epileptic activity in the cortex-NH functional complexes.…”
Section: Discussionmentioning
confidence: 97%